Routine Pressure Wire Assessment Versus Conventional Angiography in the Management of Patients With Coronary Artery Disease: The RIPCORD 2 Trial. Issue 9 (10th August 2022) - Stables, Rodney H.; Mullen, Liam J.; Elguindy, Mostafa; Nicholas, Zoe; Aboul-Enien, Yousra H.; Kemp, Ian; O'Kane, Peter; Hobson, Alex; Johnson, Thomas W.; Khan, Sohail Q.; Wheatcroft, Stephen B.; Garg, Scot; et al.
Abstract : Background: Measurement of fractional flow reserve (FFR) has an established role in guiding percutaneous coronary intervention. We tested the hypothesis that, at the stage of diagnostic invasive coronary angiography, systematic FFR-guided assessment of coronary artery disease would be superior, in terms of resource use and quality of life, to assessment by angiography alone. Methods: We performed an open-label, randomized, controlled trial in 17 UK centers, recruiting 1100 patients undergoing invasive coronary angiography for the investigation of stable angina or non–ST-segment–elevation myocardial infarction. Patients were randomized to either angiography alone (angiography) or angiography with systematic pressure wire assessment of all epicardial vessels >2.25 mm in diameter (angiography+FFR). The coprimary outcomes assessed at 1 year were National Health Service hospital costs and quality of life. Prespecified secondary outcomes included clinical events. Results: In the angiography+FFR arm, the median number of vessels examined was 4 (interquartile range, 3–5). The median hospital costs were similar: angiography, £4136 (interquartile range, £2613–£7015); and angiography+FFR, £4510 (£2721–£7415; P =0.137). There was no difference in median quality of life using the visual analog scale of the EuroQol EQ-5D-5L: angiography, 75 (interquartile range, 60–87); and angiography+FFR, 75 (interquartile range, 60–90; P =0.88). The number of clinical events was as follows: deaths, 5 versus 8; strokes, 3 versus 4; myocardial infarctions, 23 versus 22; and unplanned revascularizations, 26 versus 33, with a composite hierarchical event rate of 8.7% (48 of 552) for angiography versus 9.5% (52 of 548) for angiography+FFR ( P =0.64). Conclusions: A strategy of systematic FFR assessment compared with angiography alone did not result in a significant reduction in cost or improvement in quality of life. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01070771.